Protective effects of Naoxintong capsule alone and in combination with ticagrelor and atorvastatin in rats with Qi deficiency and blood stasis syndrome - Wei-jian Zhang; Wei-wei Su; Qing-wei Lin; Yan He; Zeng-hao Yan; Yong-gang Wang; Pei-bo Li; Hao Wu; Hong Liu; Hong-liang Yao (Taylor & Francis Group, 2020)
Context Naoxintong Capsule (NXT), a Chinese medicine, has been widely used for the treatment of coronary heart disease (CHD) in clinics. Objective This study evaluated the cardioprotective effects of NXT alone and in combination with ticagrelor (TIC) and atorvastatin (ATO). Materials and methods Qi deficiency and blood stasis rats were established by 8 weeks high fat diet feeding and 16 days exhaustive swimming and randomly divided into seven groups, that is, NXT (250, 500 and 1000 mg/kg/d), TIC (20 mg/kg/d), ATO (8 mg/kg/d), NXT (500 mg/kg/d)+TIC (20 mg/kg/d) and NXT (500 mg/kg/d)+ATO (8 mg/kg/d) group, with oral administration for 12 weeks. The contents of TC, TG, LDL-C, HDL-C, IL-1β, IL-6, IL-8, TNF-α, AST, ALT, SOD, MDA, CK-MB, LDH, TXA2, PGI2, IgA, IgG, IgM and C3 in serum were measured. Results NXT + TIC group was significantly superior to the TIC group in decreasing the levels of TC (4.34 vs. 5.54), TG (3.37 vs. 4.66), LDL-C (1.21 vs. 1.35), LDH (4919.71vs. 5367.19) and elevating SOD level (248.54 vs. 192.04). NXT + ATO group was significantly superior to the ATO group in decreasing the levels of AST (195.931 vs. 241.63), ALT (71.26 vs. 83.16), LDH (4690.05 vs. 5285.82), TXA2 (133.73 vs. 158.67), IgG (8.08 vs. 9.80), C3 (2.03 vs. 2.35) and elevating the levels of HDL-C (1.19 vs. 0.91), SOD (241.91vs. 209.49). Conclusions The present findings demonstrate that the combined use of NXT with TIC and ATO had better integrated regulating effects than TIC and ATO, respectively. The mechanism of action requires further research.